Edukasi Dan Pelatihan Herbal Serbuk Instan Untuk Menunjang Penyembuhan Tuberkulosis Di Kelurahan Maccini Sombala Kota Makassar - Pakadang, Sesilia Rante; Adhayanti, Ida (Jurnal Pengabdian Kefarmasian, 2024)
Education and Training On Instant Herbal Powder to Support The Cure of Tuberculosis in Maccini Sombala Village, Makassar CityTuberculosis infection is a disease that attacks the respiratory tract, especially the lungs, with symptoms of coughing up phlegm for more than 2 weeks. Tuberculosis treatment according to WHO standards is available free of charge at Community Health Centers, however side effects of treatment and other factors can trigger patients to drop out of treatment. Complete education on treatment and solutions to prevent side effects of treatment are the basis for this activity. Scientifically proven herbal solutions are the topic of this education. The aim of the activity to increasing participants' knowledge and providing training in making instant Miana ginger powder to support the cure for tuberculosis. Activity Method. Education and training. The target audience is the sub-district team, posyandu cadres and PKK cadres, Maccini Sombala Village, totaling 30 people. Evaluation of extension activities based on pre and post extension questionnair Evaluation of extension activities based on pre- and post-education questionnaires. Training activities are evaluated based on participants' enthusiasm for participating in the training and direct practice in making instant powder. Activity Results. The increase in participants' knowledge after counseling was 60% and there was an increase in skills based on the results of participants' practice. The obligatory output outcomes of Community service obligations include increasing knowledge, articles in pharmaceutical service media, training manuals, mini activity videos, publications in print media/online newspapers. Additional outputs include book copyrights and training products. Conclusion. there was an increase in participants' knowledge and skills. Infeksi tuberkulosis adalah penyakit yang menyerang saluran napas khususnya paru dengan gejala batuk berdahak lebih dari 2 minggu. Pengobatan tuberkulosis sesuai standar WHO tersedia gratis di Puskesmas, namun efek samping pengobatan dan faktor lainnya dapat memicu pasien putus pengobatan. Edukasi tuntas berobat dan solusi mencegah efek samping pengobatan menjadi dasar kegiatan ini. Solusi penggunaan herbal yang telah terbukti secara ilmiah merupakan topik edukasi ini.   Tujuan Kegiatan meningkatkan pengetahuan peserta dan memberikan pelatihan membuat serbuk instan miana jahe untuk menunjang penyembuhan tuberkulosis Metode Kegiatan. Edukasi dan pelatihan. Khalayak sasaran adalah tim kelurahan, kader posyandu dan kader PKK Kelurahan Maccini Sombala berjumlah 30 orang. Evaluasi kegiatan penyuluhan berdasarkan kuesioner pre dan post edukasi. Kegiatan pelatihan dievaluasi berdasarkan antusias peserta mengikuti pelatihan dan praktek langsung membuat serbuk instan. Hasil Kegiatan. Peningkatan pengetahuan peserta setelah penyuluhan sebesar 70% dan terjadi alih teknologi pembuatan herbal dalam bentuk serbuk instan. Capaian luaran wajib pengabdian masyarakat yaitu peningkatan pengetahuan, artikel pada media pengabdian kefarmasian, buku panduan pelatihan, video mini kegiatan,  publikasi pada media cetak/koran online.  Luaran tambahan berupa hak cipta buku dan produk hasil pelatihan. Kesimpulan. terjadi peningkatan pengetahuan dan keterampilan peserta.